Language change at the interfaces intrasentential and intersentential phenomena - Catasso, Nicholas; Coniglio, Marco; Bastiani, Chiara De (Linguistik aktuell ;, 2022)
"This volume offers an up-to-date survey of linguistic phenomena at the interfaces between syntax and prosody, information structure and discourse - with a special focus on Germanic and Romance - and their role in language change. The contributions, set within the generative framework, discuss original data and provide new insights into the diachronic development of long-burning issues such as negation, word order, quantifiers, null subjects, aspectuality, the structure of the left periphery, and extraposition. The first part of the volume explores interface phenomena at the intrasentential level, in which only clause-internal factors seem to play a significant role in determining diachronic change. The second part examines developments at the intersentential level involving a rearrangement of categories between at least two clausal domains. The book will be of interest for scholars and students interested in generative accounts of language change phenomena at the interfaces, as well as for theoretical linguists in general"--